Religious values in the development of children and the human capital’s formation - Sokolovskiy, Konstantin; Mustafina, Zhanar (Opción, 2019)
The study examines the relationship and seeks correlations between the human capital of individual regions of the Russian Federation and the religious beliefs of the population of these regions by using the multidimensional average method in terms of its main structural components. As a result, the state provides access to religious education for everyone, which implies an increase in the value of human capital. In conclusion, no significant differences were found in health, education, or culture indicators for the population dominated by Christianity, Islam or Buddhism.